Optimal Design and Cost Analysis of Hybrid Autonomous Distributed Generation System for a Critical Load - Sanni, Shereefdeen Oladapo; AWAISU, Abdulkadir; AJAYI, Taiwo Samuel (Politeknik Elektronika Negeri Surabaya (PENS), 2018)
One of the universal targets of the United Nations Sustainable Development Goals is affordable and clean energy. It is on this premise that this study presents the integration of PV-wind distributed generation system into an existing diesel generator powered water treatment plant in a suburban town of Wudil, Nigeria. Inadequate and epileptic supply from the grid caused the dependence of the plant on the generator. The optimal design was determined using the Hybrid Optimization of Multiple Energy Resources (HOMER) software developed by the National Renewable Energy Laboratory. Simulation results produce an optimal hybrid system which includes photovoltaic (PV) panels, wind turbines, converter, batteries and a generator with a cost of energy of 0.26 at a renewable fraction of 95%. An analysis also demonstrates that implementing this design will result in low and fairly constant fuel price in the lifecycle of the project. This will, in turn, support sustainable economic development of communities served by the water treatment plant.